Alcohol drinking and cigarette smoking in relation to risk of active tuberculosis: prospective cohort study. Issue 1 (13th October 2017) - Soh, Avril Zixin; Chee, Cynthia Bin Eng; Wang, Yee-Tang; Yuan, Jian-Min; Koh, Woon-Puay
Abstract : Introduction: Heavy alcohol consumption increases the risk of active tuberculosis (TB). However, the relation between lower levels of alcohol intake and TB risk remains unclear. We aimed to evaluate the association between alcohol intake and risk of active TB and assess whether the associations were modified by smoking status, which is another risk factor for active TB. Methods: The Singapore Chinese Health Study is a prospective cohort of 63 257 adults aged 45–74 years recruited from 1993 to 1998. Information on alcohol intake and smoking history was collected at recruitment. Active TB cases were identified via linkage with National TB Notification Registry. Results: During a mean follow-up of 16.8 years, 1249 incident cases of active TB were identified. Among non-smokers, compared with total abstinence, participants who had monthly to weekly intake of alcohol had reduced TB risk (HR 0.70, 95% CI 0.55 to 0.89), but this reduction in risk with low-dose drinking was not observed among current smokers (HR 0.96, 95% CI 0.77 to 1.18; p for interaction=0.02). Comparatively, drinking 2+ drinks daily was associated with increased TB risk among current smokers (HR 1.51, 95% CI 1.11 to 2.05). This increased risk was not observed among non-smokers (HR 0.93, 95% CI 0.49 to 1.77) and the interaction between alcohol intake and smoking status was of borderline significance (p for interaction=0.08). In joint effect, compared with those who neither smoked nor drank, the risk of active TB increased from 1.82 (95% CI 1.57 to 2.10) in current smokers who were non-drinkers to 3.16 (95% CI 2.35 to 4.24) in current smokers who also drank 2+ drinks daily. Conclusion: While low intake of alcohol may protect against active TB among non-smokers, drinking 2+ drinks daily could act synergistically with smoking to increase the risk of active TB in current smokers.